A Systematic Approach for Assessment of Attainment in Outcome-based Education. (January 2022) - Amirtharaj, S.; Chandrasekaran, G.; Thirumoorthy, K.; Muneeswaran, K.
The capabilities expected to be attained by learners, after learning a course or programme, are called course outcomes (CO) and programme outcomes (PO), respectively. The objectives of outcome-based education (OBE) are to ensure realization of grooming graduates with all the theoretical, practical and soft skills required to make them competent and industry-ready professionals. This article discusses the implementation of an assessment system for analysing the attainment of outcomes in OBE. It is a web-based application for evaluating the attainment of COs, POs and programme educational objectives (PEOs) in institutions of higher learning. Recently, OBE and choice-based credit system (CBCS) have become prevalent in institutions of higher learning. The significance and benefits of OBE and CBCS are recognized by all stakeholders, including accrediting agencies. The process for establishing and refining, the vision and mission of the institution, vision and mission of the department offering the programme, COs, POs and PEOs are discussed. The procedure and rubrics for assessing the attainment of the outcomes are also discussed. Accreditation is an honouring mechanism used to assess the standards and quality of the education offered by a programme to a student at an institution of higher learning. The article discusses a systematic approach for assessment of attainment of outcomes by graduates of a programme in an autonomous engineering college following OBE with CBCS.